Psychosocial associated factors for glycaemic control among type two diabetes mellitus patients in Kuala Terengganu - Harun, Nini Shuhaida Mat (2017)
Background: Prevalence of poor glycaemic control is significantly increased in Malaysia. There are multiple factors influencing the glycaemic control including psychosocial factors. Achieving good glycaemic control requires patients to follow a treatment regime, which involve lifelong behavioural changes, life regulation through lifestyle changes and self-management skills. This is where psychosocial factors play a role in the management of diabetes despite good medications prescribed to them. Objective: To determine the psychosocial factors associated with glycaemic control among type 2 diabetes mellitus (T2DM) patients in Kuala Terengganu. Methodology: A cross-sectional study involving 338 patients with T2DM attending two selected out-patient health clinics with highest prevalence of poor glycaemic control in Kuala Terengganu from December 2014 to June 2015. Systematic random sampling, 1:15 interval was applied. A self-administered questionnaire consists of socio-demographic background, social support score, Malay version of DASS-21 for psychological factors and Malaysian version of Medication Adherence Score (MalMAS) has been distributed to respondents.Medical background of patients were completed by the researcher. The data were analysed using descriptive statistic and logistic regression. Results: The mean age was 60.9 (+SD 10.3). 76% (257) patients has uncontrolled diabetes with mean HbA1c of 8.55% (+SD 1.95). The median social support score was 22.0 (17.0, 28.0). Through multivariable analysis using multiple logistic regression test, this study showed unemployed and pensioner patients with type 2 diabetes mellitus have protective association to have poor glycaemic control by 0.46 (p=0.035) and 0.28 (p=0.001) times respectively. Patients who perceived diabetes had interfered with their activity of daily living have 3.18 times (p=0.024) the odds to have poor glycaemic control and a patient with an increase of 1 social support score has 7% higher risk (p=0.001) to have poor glycaemic control. Conclusion: Psychosocial associated factors which were employment status, patients’ perceived diabetes had interfered with their activity of daily living, and the social support score has significant influence on the outcome of diabetes control.